Acquired platelet dysfunction with eosinophilia mimicks non-accidental injury: a case report - Anuar, Muhamad Azamin; A. Talib, Norlelawati; Misaridin, Nur Farah Izzati; Mohamed, Mossad Abdelhak Shaban; Hasan, Taufiq Hidayat (2019)
APDE is an acquired, transient bleeding disorder characterised by normal platelet counts with marked eosinophilia. It was previously known as ‘nonthrombocytopenic purpura with eosinophilia’. We report a case of a 3-year-old boy with prolonged history of spontaneous unexplained bruising which was initially investigated by Suspected Child Abuse and Neglect (SCAN) team for suspected non-accidental injury (NAI).